QUNUT AS A POSITIVE RELIGIOUS SPIRITUAL ETHIC IN THE PERSPECTIVE OF THE QUR’AN - Mujahid, Ahmad; Haeriyyah, Haeriyyah (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2021)
This article discusses qunut as a positive religious-spiritual ethic in the perspective of the Qur’an. The method used is the thematic interpretation method. The results showed that the essence of the meaning of qunut as the religious-spiritual ethics of the Quran is obedience, obedience, submission and slavery full of earnestness, specialty, humility and love for Allah and to the Messenger of Allah. The nature of qunut with such a meaning, true becomes the personality character of every individual Muslim. Qunut character should also be a building of life in spousal or domestic relations and social-community life. Keywords: Qunut; Positive Religious-spiritual ethics